HADITS-HADITS NABI SAW. TENTANG PEMBINAAN AKHLAK - Nixson Husin (UIN SUSKA RIAU, 2015)
The noble moral is the main foundation in build the personal character of a Muslim. To realize these morals in life, the need for a coaching continue. This paper is in an effort to look carefully and clearly prophetic narrations about coaching morals for generations of Muslim children. This paper will also describe how the prophet in fostering the morals of the people, so that the mission of the leadership in the earth remains biased to run. To build a commendable character and seriousness necessary mental starting from myself, family until then social environment. Finer reflected in all actions, words, actions and attitudes that can give benefit for others, give peace to all beings on this earth.